Protective potential of selected microbial and non-microbial biostimulants against Zymoseptoria tritici leaf blotch in winter wheat as affected by the form of N supply - Göbel, Markus; Dulal, Samiksha; Sommer, Lea; Weinmann, Markus; Mamun, Abdullah Al; Ahmed, Aneesh; Sujeeth, Neerakkal; Mai, Karin; Neumann, Günter; Müller, Torsten; Bradáčová, Klára (Frontiers in Plant Science, 2024)
The production of high-quality food for the growing world population on the one hand and the reduction of chemical-synthetic pesticides on the other hand represents a major challenge for agriculture worldwide. The effectiveness of a combination of microbial and non-microbial biostimulants (BSs) with various nitrogen (N) forms in pathogen defense is a promising, but still a poorly understood bio-based alternative for crop protection. For this reason, nitrate and stabilized ammonium fertilizer both combined with a consortium of Pseudomonas brassicacearum, Bacillus amyloliquefaciens and Trichoderma harzianum as soil treatment or with a mixture of seaweed extract (Ascophyllum nodosum) together with chitosan amended micronutrient fertilizer as foliar spray application were compared under controlled greenhouse conditions. Furthermore, a combination of microbial and different non-microbial BSs (seaweed extracts + chitosan) and micronutrients with nitrate or with stabilized ammonium fertilizer were tested under field conditions to improve nutrient availability, promote plant growth, and suppress Zymoseptoria tritici (Zt) in winter wheat. While plant-protective effects against Zt by the microbial consortium application could be observed particularly under ammonium fertilization, the application of seaweed extract-chitosan mixture expressed plant defense against Zt more strongly under nitrate fertilization, both under controlled greenhouse conditions. In the field trial, the combination of microbial consortium with seaweed extract-chitosan mixture together with micronutrients zinc (Zn) and manganese (Mn) showed positive effects against Zt under ammonium fertilization which is consolidated by increased metabolic activities. Furthermore, the additional input of Zn and Copper (Cu) from the chitosan application improved the micronutrient status by minimizing the risk of Zn and Cu deficiency under controlled and field conditions. The use of BSs and the inoculation of Zt did not show any effects on plant growth and yield neither under controlled greenhouse conditions nor in the field. Summarized, microbial and non-microbial BSs separately applied or even combined together as one treatment did not influence plant growth or yield but made a positive contribution to an N form dependent pathogen defense.